Optimization of high density long duration transportation of silver carp (Hypophthalmichthys molitrix) and rui (Labeo rohita) fingerlings - Hasan, Mahmud (Dhaka University Journal of Biological Sciences, 2018)
The effects of density (50, 55 and 60 kg fingerlings/drum of 200 litre) on the mortality and essential water quality variables were assessed for silver carp Hypophthalmichthys molitrix fingerlings in a simulated transport experiment. The second experiment involved the determination of the effects of knowing the optimum loading density 50 kg/drum fingerlings on the mortality and water quality in silver carp advanced fingerlings for standard 8 hours transport simulation. Six hours of simulation duration resulted in less than 1% mortality and 8 hours caused about 6%. Third experiment with highest density 60 kg/drum fingerlings at 500 g/l of advanced rui (Labeo rohita) fingerlings was used for a period of 6 hours since the quality of the transport medium was deteriorated due to regurgitated stomach contents. The fingerlings were unconditioned and fed. Level of immediate mortality was only nearly 3% at 6 hours of simulation duration. This study has clearly demonstrated that the optimum loading of silver carp fingerlings per drum is 50 kg. The minimum concentration of dissolved oxygen (DO) concentration for maximum survival is 2 mg/l for silver carp fingerlings. Silver carp advanced fingerlings can be transported for 8 hours duration by using 2 phenoxyethanol at the concentration of 115 μl/l with oxygen injection. Rui advanced fingerlings can be transported at 60 kg/drum (500 g/l) for 6 hrs duration even if the fingerlings are unconditioned. Dhaka Univ. J. Biol. Sci. 27(1): 9-16, 2018 (January)